2006
DOI: 10.1080/13651500500443365
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric characteristics of 100 nonviolent suicide attempters in Hungary

Abstract: This study supports previous international and Hungarian findings on the high prevalence and comorbidity of Axis I mental disorders among persons with recent nonviolent suicide attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
4
9
1
Order By: Relevance
“…Two thirds of our sample were females. Many previous studies have demonstrated higher rates of suicide attempts in females (54%–69%) (Lecrubier, 2001; Rihmer et al, 2006); the rates of first suicide attempt in our study were consistent with those findings. The reported female/male ratio of completed suicide (Altindaǧ et al, 2005) was also similar to values reported in this present study; however, the patients included in our study were serious cases admitted to intensive care units, and the number of females between the ages of 15–24 years was higher compared to males, which could explain higher rates of completed suicides in this geographical region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two thirds of our sample were females. Many previous studies have demonstrated higher rates of suicide attempts in females (54%–69%) (Lecrubier, 2001; Rihmer et al, 2006); the rates of first suicide attempt in our study were consistent with those findings. The reported female/male ratio of completed suicide (Altindaǧ et al, 2005) was also similar to values reported in this present study; however, the patients included in our study were serious cases admitted to intensive care units, and the number of females between the ages of 15–24 years was higher compared to males, which could explain higher rates of completed suicides in this geographical region.…”
Section: Discussionsupporting
confidence: 93%
“…Prospective studies have also demonstrated that previous suicide attempts increase the risk of future suicidal gestures (Oquendo, Currier, & Mann, 2006; Zweig & Hinrichsen, 1993). In particular, past history of a suicide attempt(s) with an accompanying untreated mood disorder are strong determinants of future completed suicides (Gibb, Beautrais, & Fergusson, 2005; Rihmer et al, 2006; Suominen et al, 2004). Therefore, examining the suicide attempt may serve to help understand and prevent future completed suicides.…”
mentioning
confidence: 99%
“…Rihmer et al [95] reported 46% anxiety disorders and 27% substance use disorder partly in the same patient population at a later point of time and presented 60% multiple comorbidities with 2 or 3 disorders occurring concurrently with the above-mentioned diagnoses. Adolescent clinical studies regularly find a high prevalence of major depression and substance use (drug Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as many as two-thirds of people with depression reports suicidal ideation, 10-15% commit suicide and 60-70% suicide victims have had severe depression before completed suicide (Woo et al 2014). Regardless the decline in suicide mortality, in majority of countries with high baseline suicide rates, suicidal behavior still manifests among patients with mood disorders in state-dependent order (Latalova et al 2014, Rihmer et al 2006, Suominen et al 2004). …”
Section: Introductionmentioning
confidence: 99%